Shorting And Drying Technology Unit For Improving The Effectiveness Of Black Onion Process - Sebayang, Kerista; Siregar, Amir Hamzah; Sianturi, Herty Afrina; Mirsan, Erni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
In 2016, the development of Gempar Tunggal Micro Small and Medium Enterprises (MSMEs) that involved in the processing of black onions began. The raw materials are obtained from the Medan City market center, but sometimes it also come from Brebes and Semarang. The goods manufacture that resulted are sold to Aceh, Kalimantan and Sulawesi. However, because it was a home industry, the manufacturing system that was developed still very simple. Therefore, some weakness were identified, in particular the percentage of damaged or defective finished goods reaching 25 percent before its sold, various levels of maturity and work processes and supervision that drained attention and energy. In addition, the cost of using electricity is also high. It was found from the literature study by the Abdimas team of USU that there are 3 parameters that affect the processing of onions, namely garlic which is sensitive to temperature, humidity and exposure period of temperature and humidity. Often, due to the unequal size of the raw onion amount, the maturity of the onions is not homogenous distributed made the bigger the raw material of the onion impacted the faster it will ripen. Another problem that found during manufacturing process is the water vapor was not completely evaporated from the furnace. Basic technology that was developed by Abdimas USU team, namely the manual gravity onion sorting and drying unit was already used by Partners in the production process. As the result, it was successfully reducing broken onions. Lastly, homogenous maturity due to dividing process the onions by scale obtained.